Simulation of Three-Pulse-Echo and Fluorescence Depolarization in Photosynthetic Aggregates - Meier, Torsten; Zhang, W.M.; Chernyak, V.; Mukamel, S. (Philosophical Transactions of the Royal Society of London. Series A: Mathematical, Physical and Engineering Sciences)
Femtosecond spectroscopies of chlorophyll dimers and the LH2 antenna complex are calculated using a theory that incorporates the effects of two–exciton states, static disorder and coupling of excitons to phonons with an arbitrary spectral density. Applications are made to pump–probe and echo peak–shift measurements in the B820 dimers, and to fluorescence depolarization in the B850 system of the LH2 antenna of purple bacteria.